Pemanfaatan Sedimen Sungai Untuk Bahan Baku Unfired Bricks (Bata Tanpa Bakar) - Didit Puji Riyanto; Suhardi -; Wahyu Prasetyo; Pranu Arisanto (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
The land use change in a watershed cause erosion resulting in sedimentation in river channels. Physically treatment of sedimentation requires a considerable cost, hence it is necessary to find another alternative treatment, i.e. by utilizing river sediment for building materials. Brick is a building material that is widely produced and used by the society. To provide solutions for sediment reduction, it is necessary to do a research on the utilization of river sediment for brick raw materials. In this study, the utilization of sediment into bricks was proposed in the form of Unfired Bricks. Raw sediment material will be mixed with cement and sand with a certain composition to increase the compression strength of brick in order to meet one of the SNI requirements, i.e. 15-2094-2000 or SNI 03-0349-1989. Results found that the addition of cement and sand treatment can increase the compressive strength of the brick up to 44,176 kg/cm² at the age of 14 days. However, the compression strength test results are still below the compression strength of Red Brick requirements in accordance with SNI 15-2094-2000 where the minimum compression strength of brick is 50 kg /cm², but it qualify for the compression Strength Concrete Brick SNI 03-0349-1989 for the quality level of grade III with a minimum of 40 kg / cm² and grade IV with a minimum of 25 kg / cm²